2019
DOI: 10.1016/j.joca.2019.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of extracorporeal shockwave on rat chondrocytes and temporomandibular joint osteoarthritis; preclinical evaluation with in vivo 99mTc-HDP SPECT and ex vivo micro-CT

Abstract: Objective: Extracorporeal shockwave therapy (ESWT) has been shown to have chondroprotective effects on arthritic diseases. We investigated the effects of ESWT on temporomandibular joint osteoarthritis (TMJOA) using rat chondrocytes and TMJOA rat models. Design: Cell viability and expression of pro-inflammatory cytokines, cartilage degradation, and apoptosis markers were measured in control, monosodium iodoacetate (MIA)-treated and ESWT plus MIA-treated chondrocytes in vitro, and intra-articular MIA injection (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 36 publications
0
19
0
1
Order By: Relevance
“…Very recently, animal model studies have increasingly demonstrated the efficacy of ESWT for OA [16,17,19]. However, few studies have explored the clinical application of ESWT, probably due to a lack of mechanistic clarity and scientific evidence [48]. OA is characterized by the main features of articular cartilage degeneration and subchondral bone remodeling and cardinal symptoms of pain and restricted motion in the affected joints.…”
Section: Extracorporeal Shockwave Treatment For Osteoarthritismentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, animal model studies have increasingly demonstrated the efficacy of ESWT for OA [16,17,19]. However, few studies have explored the clinical application of ESWT, probably due to a lack of mechanistic clarity and scientific evidence [48]. OA is characterized by the main features of articular cartilage degeneration and subchondral bone remodeling and cardinal symptoms of pain and restricted motion in the affected joints.…”
Section: Extracorporeal Shockwave Treatment For Osteoarthritismentioning
confidence: 99%
“…ESWT may also exert chondroprotective effects in OA models by restoring the production of IL-10 and TNF-α in chondrocytes to normal levels [55]. Kim et al [48] investigated effects of ESWT on temporomandibular joint osteoarthritis (TMJOA) in Rat OA models, and found ESWT treatment could increase cell viability significantly and decrease expression of cartilage degradation markers including MMP3 and MMP13. Changes in cytochrome c and cleaved caspase-3 levels relative to procaspase-3 were also decreased by ESWT, which showed a significant decrease in pro-inflammatory and cartilage degradation markers.…”
Section: Effect Of Eswt On Cartilagementioning
confidence: 99%
“…Recent work has identified a battery of proteins that regulate processing (either positively or negatively) by binding to miRNA precursors 27 . The TNF gene plays a key role in TMJOA development, as previously reported 28,29 . Interestingly, TNF-α, one of the essential inflammation cytokines present at substantially higher levels in the TMJOA synovium than in the control synovium ( Fig.…”
Section: Mir-330-3p Directly Targets the Tnf Gene And Regulates Tnf-αmentioning
confidence: 60%
“…r-ESW has been demonstrated to clinically accelerate the healing of meniscus tears and muscle injuries and has chondroprotective effects [ 7 , 35 ]. Intriguingly, r-ESW can even strengthen the stemness of stem cells through its unique mechanical characteristics [ 4 , 36 ].…”
Section: Discussionmentioning
confidence: 99%